Harriet Tubman : myth, memory, and history - Sernett, Milton C., 1942- (Slavery in America and the world: history, culture & law., 2007)
An exploration of the way history, meaning, and memory have interacted in the process of transforming Harriet Tubman into an American icon and a figure of inspiration like Abraham Lincoln or Fredrick Douglass.